Preparing the Previously Married for Second Marriage - Rolfe, David J. (The Journal of pastoral care, 1985)
Observes that as more and more couples wishing to get married in the Church are entering a second marriage situation, pastoral ministry requires different approaches than would be used in working with a couple who had no previous marriage experience. Outlines specific approaches which assist clergy and previously married persons assess readiness for second marriage. Gives case illustrations and provides interview guidelines in securing information on economic, legal, co-parental, community, emotional, and psychic areas relevant to the preparation.